Applications of radiative sky cooling in solar energy systems: Progress, challenges, and prospects. (May 2022) - Hu, Mingke; Zhao, Bin; Suhendri,; Ao, Xianze; Cao, Jingyu; Wang, Qiliang; Riffat, Saffa; Su, Yuehong; Pei, Gang
Abstract: The dynamic energy balance on the earth is jointly governed by solar energy harvesting and radiative sky cooling. Mainstream solar energy technologies, including photovoltaic conversion (PV), photothermal conversion (PT), and photovoltaic/thermal conversion (PV/T), as well as concentrated solar power (CSP) generation, have experienced significant progress after decades of developments. Recently, radiative cooling also saw significant advancements attributed to breakthroughs in material sciences and technologies. Though the energy transfer direction of solar energy collection and long-wave (above 3 μm) heat dissipation are poles apart, it is possible to combine the two mechanisms in one single system to exploit more energy from the universe. Radiative cooling has proved to be an effective way to either increase the PV efficiency by passively lowering the operating temperature of PV modules, or extend the working period of PT and PV/T collectors to nighttime and cold days via adding an extra passive cooling working mode, or enhance the thermal-to-power efficiency of CSP plants through declining the condensing temperature of the power block. This work conducts a comprehensive review and discussion on the history and recent advancements regarding the application of radiative cooling in different types of typical solar energy systems. Besides, existing challenges and possible opportunities involving combining the two ultimate renewable energy from outer space are concluded. This paper aims to provide a general summarization and possible guidance on the current status and future developments of radiative sky cooling applications in solar energy systems. Highlights: Principles of radiative cooling and four solar energy technologies are introduced. Applications of radiative cooling in these solar energy systems are reviewed. Some current challenges and potential applications are presented and discussed.